1980
DOI: 10.1071/zo9800249
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Adrenal Gland in the Tammar Wallaby, Macropus Eugenii (Desmarest) (Marsupialia: Macropodidae).

Abstract: The adrenal of the male tammar wallaby first appears at day 21 of embryogenesis as a nodule of tissue lying close to the anterior pole of the kidney. The nodule consists of adrenocortical tissue in that its cells contain an active 3 beta ol-steroid dehydrogenase from about day 22 of embryogenesis. From day 22 of embryogenesis until at least day 20 of pouch life a sympathetic nerve plexus is adpressed to the medial side of the adrenal. Cells migrate from the plexus through pores in the capsule of the gland and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…A t this stage of development a thin cortex incompletely surrounds a large medulla (Leslie, 1979). A similar finding has been reported for the tammar wallaby since, although some cells display chromaffin reaction on day 7 of pouch life, a distinct medulla is not found until day 60 (Call et al, 1980). After studying the hour of birth in rats, Lincoln and Porter (1976) suggested that the fetus may determine the day of birth in this species through the maturation of the pituitaryadrenal-placental axis, but the mother may hour of birth.…”
Section: Discussionsupporting
confidence: 74%
“…A t this stage of development a thin cortex incompletely surrounds a large medulla (Leslie, 1979). A similar finding has been reported for the tammar wallaby since, although some cells display chromaffin reaction on day 7 of pouch life, a distinct medulla is not found until day 60 (Call et al, 1980). After studying the hour of birth in rats, Lincoln and Porter (1976) suggested that the fetus may determine the day of birth in this species through the maturation of the pituitaryadrenal-placental axis, but the mother may hour of birth.…”
Section: Discussionsupporting
confidence: 74%
“…Beyond this time there is a marked increase in milk consumption and body weight, so that by 200 days the average intake of milk is about 50 ml/day (Green, 1984). These changes in milk intake and composition probably reflect the increasing energetic requirements of the young which, between 100 and 200 days, achieves homeostasis; its thermoregulatory and metabolic functions develop (Setchell, 1974;Paton & Janssens, 1981) and the thyroid, adrenal and pituitary glands begin to secrete their respective hormones (Setchell, 1974;Call, Catling & Janssens, 1980;Wilkes, 1984). Furthermore, it is during this period that the incremental growth rate of the young accelerates (W. E. Poole, personal communication), closely paralleling the accelerated growth of the active mammary gland (Stewart, 1984) and the rising level of plasma prolactin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their small size and immaturity at birth, the same is true in tammars. The fetal adrenal is morphologically developing from day 21 of gestation (Renfree, 1972;Call et al, 1980) and by day 24 cortisol is easily measurable in fetal blood. Fetal adrenal cortisol production then increases in the last 2 days of gestation (Ingram et al, 1999) before falling post-partum ( Figure 5).…”
Section: The Trigger For Birth -Fetal Cortisolmentioning
confidence: 99%